Short- and long-term changes in neurological, behavioural, and blood biomarkers following repeated mild traumatic brain injury in rats—potential biological sex-dependent effects - Rodrigo Moraga-Amaro; Oscar Moreno; Jordi Llop; Marion Bankstahl; Marion Bankstahl; Jens P. Bankstahl (Frontiers in Molecular Neuroscience)
IntroductionChronic traumatic encephalopathy (CTE) is a progressive neurodegenerative disease resulting from repeated mild traumatic brain injuries (rmTBI). The necessity for diagnosis of CTE, which can so far only be confirmed after post-mortem, is a pressing need. New approaches to early diagnose this disease are crucial to facilitate the translation of novel treatment strategies to the clinic. Several studies have found suitable candidate biomarkers, but the results are not straightforward. As biological sex is suggested to be a major confounding factor, we explored how sex influences behavioural and candidate blood biomarkers during CTE-like progression following experimental rmTBI.MethodsTo induce CTE-like development, we subjected male and female rats to three mTBIs at a 5-day interval. We then monitored and analysed differences in neurological, behavioural, and physiological parameters up to 12 weeks after the injuries—both by sex and grouped—and underwent further analysis using generalised estimated equation (GEE). To determine long-term changes in tau aggregation as a hallmark of CTE, we used [18F]-florzolotau (florzolotau) autoradiography in brain slices.ResultsBoth short-term weight gain and time-to-right after rmTBI were increased in grouped animals, with male rats showing more prominent changes. The neurological state was impaired after each mTBI and still 12 weeks later, independent of the sex. A protracted anhedonic-like behaviour due to rmTBI was found at the group level only at week 2 but remained continuously present in male rats. While spatial memory was not impaired, male rats showed increased anxiety-like behaviour. Moreover, neuron-specific enolase (NSE) was elevated in the blood 1 day after rmTBI, but only in females. On the contrary, blood p-tau was increased 3 days after rmTBI only in males. In addition, male rats showed significantly increased florzolotau binding in the brain after 12 weeks, suggesting brain contusion causes increased tau aggregation. Interestingly, brain neurofibrillary tangles (NFTs) at 12 weeks after rmTBI showed a strong correlation with the neurological state at 1 day after rmTBI.DiscussionTaken together, our findings suggest that male rats may be more susceptible to short-and long-term consequences of rmTBI in the applied model. These sex differences should be considered when translating preclinical biomarker candidates to the clinic. Understanding these differences could guide the diagnosis and treatment of CTE in a personalized manner, offering hope for more effective treatments in the future.